2014
DOI: 10.1016/j.cub.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

The Logic of Circadian Organization in Drosophila

Abstract: SummaryBackgroundIn the fruit fly Drosophila melanogaster, interlocked negative transcription/translation feedback loops provide the core of the circadian clock that generates rhythmic phenotypes. Although the current molecular model portrays the oscillator as cell autonomous, cross-talk among clock neurons is essential for robust cycling behavior. Nevertheless, the functional organization of the neuronal network remains obscure.ResultsHere we show that shortening or lengthening of the circadian period of loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 37 publications
7
71
0
Order By: Relevance
“…One possibility is based on the multicellular organization of the circadian neural network driving behavioral rhythms. Although it appears that under normal circumstances the PDF-expressing s-LNvs are the key pacemaker neurons driving free-running behavioral rhythms, recent findings suggest that the circadian neural circuitry in the Drosophila brain is less hierarchical than previously thought and that neurons other than the s-LNvs can make strong contributions to behavioral periodicity (64,65). Within this framework, the S826A/S828A mutations might speed up the clockworks in only a few non-s-LNv cells, an event that would somehow alter the circadian neural hierarchy such that behavioral rhythms would be governed by the faster-running cells, not the s-LNvs.…”
Section: Discussionmentioning
confidence: 95%
“…One possibility is based on the multicellular organization of the circadian neural network driving behavioral rhythms. Although it appears that under normal circumstances the PDF-expressing s-LNvs are the key pacemaker neurons driving free-running behavioral rhythms, recent findings suggest that the circadian neural circuitry in the Drosophila brain is less hierarchical than previously thought and that neurons other than the s-LNvs can make strong contributions to behavioral periodicity (64,65). Within this framework, the S826A/S828A mutations might speed up the clockworks in only a few non-s-LNv cells, an event that would somehow alter the circadian neural hierarchy such that behavioral rhythms would be governed by the faster-running cells, not the s-LNvs.…”
Section: Discussionmentioning
confidence: 95%
“…Menegazzi et al also confirmed a preliminary observation of Vanin et al (2012), where PER and TIM cycle in the Dorsal Neurons (DNs) in advance of the other neurons, suggesting a faster oscillation in these cells. This has been experimentally supported in the laboratory using a functional assay of the DNs in which these cells' influence on the clock cellular network is amplified, resulting in a shorter behavioral period (Dissel et al, 2014). Finally, while locomotor behavior in the wild appears to be dominated by the temperature cycle, the natural light cycle appears to be the more dominant zeitgeber for the cellular expression of PER and TIM (Menegazzi et al, 2013;Vanin et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Restoring a wild-type copy in the morning neurons of na mutant flies does not restore wild-type rhythmic behavior, while restoring na in the evening neurons does (Lear et al 2005a). Finally, interfering with the neuronal clocks through the overexpression of a dominant-negative CLK mutant in the evening neurons severely weakens behavioral rhythmicity in a light/dark cycle and results in arrhythmic flies in constant dark conditions (Dissel et al 2014). Therefore, the LNds, while retaining some autonomy of their own clock, are responsible for communicating instructions from the s-LNvs (by way of PDF) to downstream targets to regulate rhythmic behavior.…”
Section: The Dorsal Lateral Neurons and The Fifth S-lnvmentioning
confidence: 99%